UTILIZING GOOGLE DRIVE AS A PERSONAL DIGITAL LIBRARY - Alvin Febrianto (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2022)
Libraries have another form called digital libraries. In line with the development of information technology that has entered human life, it has brought changes to the library system. The desire to have library resources that can be accessed anywhere and anytime also encourages the existence of digital libraries. By utilizing a digital library-based information system, everyone can obtain appropriate and useful reading sources. The impracticality of the conventional library system is that one has to go to the location first, which is very impractical. This situation makes digital libraries one of the solutions that can be built to bridge these weaknesses. The method used in this study is a qualitative descriptive method. From the results and discussion obtained the steps for creating an account, digital library design, how the system works, and the appearance of digital libraries. The hope of this research is that the library system created can be used by anyone to support an easy, inexpensive, and paperless information system.